Effect of Tobacco Cessation on Weight in a Veteran Population - Crystal Zhou; Nicole G. Tran; Timothy C. Chen (SAGE Publishing, 2020)
Introduction/Objectives: Weight gain concerns remain a barrier to tobacco cessation. Literature suggests that weight gain can occur after stopping tobacco, but continuing tobacco can have far worse outcomes. Limited information is available regarding weight gain in military personnel. The objective of this study was to evaluate weight change in veterans that stopped tobacco for a minimum of 12 months enrolled in a pharmacist managed telephone tobacco cessation clinic (PMTTCC). Methods: A retrospective analysis of veterans who had been tobacco-free for 12 months enrolled in a PMTTCC were included in this analysis. Primary outcomes were change in weight (kg) and body mass index (BMI) from baseline. Descriptive data were utilized where appropriate and paired t -tests were utilized for the primary outcomes. Results: Seventy-seven patients were screened and 10 were excluded. Sixty-seven veterans met inclusion criteria and were mostly male (91%, n = 61) and Caucasian (74.6%, n = 50). At 12 months post cessation, the mean weight gain was (1.81 kg ± 6.83, P  = .03) and BMI (0.51 ± 2.23 kg/m 2 , P  = .06). Conclusions: Veterans appeared to have minimal weight gain despite statistical significance and no statistical change with BMI after 12 months of being tobacco-free. Results suggest that the long-term weight gain is minimal, and a comprehensive tobacco cessation program can be helpful to improve weight outcomes.